C-reactive protein in patients with coexistent periodontal disease and acute coronary syndromes - Maciej R. Czerniuk (journal of clinical periodontology, 2006)
Aim: To evaluate periodontal disease (PD) influence on changes in high-sensitivity C-reactive protein (hsCRP) concentrations in patients with acute coronary syndromes and coexistent PD. Materials and Methods: Dental examinations were carried out in a group of 50 consecutive patients, less than 60 years old, hospitalized as a result of acute coronary syndromes. The patients were divided into two groups on the basis of own-constructed combined PD score (group 2: more advanced; and group 1: less advanced PD) as well as clinical attachment loss (CAL) – group 4: CAL 43 mm; group 3: CAL 43 mm. Blood samples for hsCRP estimation were taken at admission, after 10/12 days and long term after acute coronary syndromes. Results: A statistically significant decrease in hsCRP was observed among three consecutive blood sample examinations in groups 2 and 4, whereas it was only seen between examination 1 and examination 2 in groups 1 and 3. Conclusions: Although no statistically significant difference of hsCRP was found between studied groups, patients with less advanced PD, either estimated with the use of own-constructed combined score or on the basis of CAL, have significantly longer diminution of inflammatory response monitored with hsCRP concentrations.